An antibody uniquely binding short 2′-O-methyl RNA oligonucleotide duplexes: formation and recognition of target duplexes on cell surfaces - Dunn, Ian S.; Lawler, Matthew M.; Fagundes, Leah; Simoes Junior, Milto; Mangold, April; Rinaldi, Domenic; Rose, Lenora B.; Kurnick, James T. (Frontiers in Immunology, 2026)
With the primary aim of generating antibody tools useful for diagnostic and therapeutic applications relevant to oligonucleotide-templated reactions, an scFv filamentous phage library was screened using a specific 2′-O-methyl RNA template:oligonucleotide click reaction complex as the target structure. Such an antibody would not be expected to recognize any naturally occurring biological molecules. Two promising candidate scFv clones were converted into human IgG1 antibodies for further characterization. Surprisingly, although the best antibody (IgG1-DS5) was bound to the original selection complex, its recognition preference was shown to be directed toward short 2′-O-methyl RNA duplexes without click modifications. The IgG1-DS5 antibody showed no binding to the separate single strands comprising the recognized duplex, nor to the corresponding duplexes with RNA or DNA template strands. Versions of the target 2′-O-methyl RNA duplex with divergent sequences were also not recognized by IgG1-DS5. The unexpected binding properties of the IgG1-DS5 antibody were directed toward potential applications based on the molecular proximity of tethered single strands. Initially, SKBr3 cells were coated with biotins by means of surface azide metabolic labeling with peracetylated N-azidoacetylmannosamine, followed by treatment with a click-reactive DBCO-PEG4-biotin compound. Subsequent cell treatment with the tetravalent biotin-binding protein neutravidin (NAV), carrying subsaturating levels of biotinylated 2′-O-methyl RNA target duplexes, showed strong IgG1-DS5 staining on cell surfaces. These observations were extended with biotinylated anti-EGFR antibody linked with biotinylated 2′-O-methyl RNA single strands, also by means of the NAV protein as an adaptor. Flow cytometry analysis showed that DS5 antibody binding was only obtained when combinations of separate preparations of antibodies carrying top and bottom target strands were applied sequentially to EGFR-positive cells. These results show that proximity-based surface annealing of the IgG1-DS5 antibody target single strands can act to define cell populations with a surface marker of sufficient density. Where IgG1-DS5 is derivatized with either a fluorescent moiety or a cytotoxic drug, this antibody may find application in diagnostic or therapeutic tumor targeting.